The Philippine commercial banking industry profile structure and performance. - Pediongco, Carmela Sison (1996.)
This study described the profile and analyzed the performance and structure of commercial banking industry in the Philippines. The researcher used measures of stability, capital adequacy, solvency and intermediation ratio in analyzing the performance. The measure of degree of industry concentration, using Horfindah!-Hirshman Index and the four-Firm ratio were used to describe the structure., Studies related to commercial banks and other banks were used as secondary data. A section of this paper reviewed the related literatures. Results showed that the performance of the industry was stable but risky. The degree of concentration of the industry became higher. Foreign banks were measured to have higher solvency and adequate capital. Ordinary commercial banks had higher intermediation ratio. Since the scenario of banking industry rapidly changed, the researcher recommended measures on how to improve the system.
Thesis (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Banks and Banking -- Philippines